2007
DOI: 10.1164/rccm.200610-1410oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Hyperresponsiveness in Allergically Inflamed Mice

Abstract: Rationale: Allergically inflamed mice exhibit airway hyperresponsiveness to inhaled methacholine, which computer simulations of lung impedance suggest is due to enhanced lung derecruitment and which we sought to verify in the present study. Methods: BALB/c mice were sensitized and challenged with ovalbumin to induce allergic inflammation; the control mice were sensitized but received no challenge. The mice were then challenged with inhaled methacholine and respiratory system impedance tracked for the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
123
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 32 publications
9
123
0
1
Order By: Relevance
“…With aerosol, H increases substantially, even in control animals, and in allergically inflamed mice the hyperresponsiveness in H is proportionally greater than that in either R or G, even when the fractional increases in R are not as great as in the present study (38). We have shown that these increases in H are due mainly to closure of small airways in the lung periphery (22,38). Interestingly, H was clearly somewhat elevated in the acutely inflamed animals (Fig.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…With aerosol, H increases substantially, even in control animals, and in allergically inflamed mice the hyperresponsiveness in H is proportionally greater than that in either R or G, even when the fractional increases in R are not as great as in the present study (38). We have shown that these increases in H are due mainly to closure of small airways in the lung periphery (22,38). Interestingly, H was clearly somewhat elevated in the acutely inflamed animals (Fig.…”
Section: Discussionsupporting
confidence: 40%
“…To produce an acute inflammation, mice were sensitized with an intraperitoneal injection of ovalbumin (20 g in 2.25 mg alum) on days 0 and 14. They were challenged on each of days 21,22, and 23 by being placed in a compartmentalized aerosolization chamber and exposed to ovalbumin aerosol (1% in phosphate-buffered saline) for 30 min. Airway responsiveness to a bolus intravenous injection of 137 g/kg methacholine (0.074 mg/ml in ϳ40 l saline) was measured (see below) on day 25.…”
Section: Animal Groupsmentioning
confidence: 99%
“…Two methods of volume segmentation, as described by others [1][2][3][4]13], were performed, in order to assess the advantages of and similarities between these methods. In Method 1, the thoracic volume was segmented by defining a region of interest that encapsulated the entire lung by manually outlining the ribcage and chest wall using characteristic landmarks and interpolation.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to asthma, research utilising CT immediately following sacrifice, i.e. ex vivo, has elegantly contributed to establishment of the role of airway closure on hyperreactivity in mice undergoing acute allergic inflammation [4]. The ability to acquire CT data in a model of allergic asthma in vivo would be a step towards noninvasive assessment, utilising the same tools that are available in humans [5,6].…”
mentioning
confidence: 99%
“…The combination of micro-CT imaging and constant phase model parameters has also been used to analyze animal models of lung disease before. In particular, Lundblad et al (2007) qualitatively analyzed ex vivo micro-CT images in a mouse model of allergical inflammation and combined it with measurements of tissue elastance. In this work, we propose to use quantitative airway measurements since this approach is likely to provide valuable information to better understand the morphology and function of lungs affected by diseases such as emphysema and inflammation.…”
mentioning
confidence: 99%